14, 15-Secopregnane-type C21-steriosides from the roots of Cynanchum stauntonii. (June 2017) - Yu, Jin-Qian; Lin, Ming-Bao; Deng, An-Jun; Hou, Qi; Bai, Jin-Ye; Li, Zhi-Hong; Ma, Lin; Zhang, Zhi-Hui; Yuan, Shao-Peng; Jiang, Ren-Tao; Qin, Hai-Lin
Abstract: Nine 14, 15-secopregnane-type C21 -steriosides, stauntosides U, V, V1 -V3, W and C1 -C3, as well as two known C21 -steriosides, were isolated from the roots of Cynanchum stauntonii . Stauntosides U, V and V1 -V3 share the same basic structural features of 8 α :14 α, 14:16, 15:20, 18:20-tetraepoxy-14, 15-secopregn-6-ene-3 β, 5 α, 9 α -triol, with the numbering system following that of C21 -pregnanes. The aglycones of stauntosides U, V and V1 -V3 are classified into two subcategories, the 5, 9-dihydroxy groups and 5 α :9 α -peroxy bridge, according to the oxidative states of the two hydroxy groups at the C-5 and C-9 positions. The anti-inflammatory activity of the major compounds was assessed in an in vitro inflammatory model of mouse peritoneal macrophages using IC50 values of the inhibition of nitric oxide (NO) production as an indicator. Stauntosides V1 and V3 exhibited target activity with IC50 values of 9.3 μM and 12.4 μM, respectively, compared with dexamethasone, which was used as a positive control. Graphical abstract: IC50 of anti-inflammatory activies: stauntoside V1 12.4 μM; stauntoside V3 9.3 μM. Highlights: Nine 14, 15-secopregnane-type C21 -steriosides were isolated from Cynanchum stauntonii . An unusual 14, 15-secopregnane with 5:9-peroxy bridge moiety was characterized. Two sugar moieties composed of deoxysugars were characterized. Active compounds selectively inhibited production of nitric oxide. Bioactive C21 -steriosides underlie the traditional application of C. stauntonii .